Mechanical Behavior of Dam Foundation with Vertical Sand Drain, Case Study: Sombar Dam - Mahmood, Mohammed Shaker; Akhtarpour, Ali; Alali, Ameer Abdulridha Ajmi (Journal of Engineering and Technological Sciences, 2019)
Installing vertical sand drains is a traditional dam foundation consolidation solution that is economical and provides good drainage efficiency. Vertical sand drains can shorten the path of water flow inside the soil and speeds up soil consolidation. This study investigated the effect of sand drains in the foundation of the Sombar Dam in Iran on its mechanical behavior. The Sombar Dam is a project to control flooding and provide agricultural water to Gholaman city in northeastern Iran. The investigation included the mechanical behavior of the dam with vertical sand drains. The studied parameters were drain diameter, depth and spacing in addition to the vertical-to-horizontal permeability ratio (ky/kx) of the foundation soil during the time of construction of the dam using a Mohr-Coulomb (MC) model in the software application GeoStudio. The results revealed that reducing the drain spacing (increasing the number of drains) and increasing the depth and diameter of the drains led to an increase of the settlement rate (up to 90%) and the stability of the dam over a shorter period of time (24 months) compared to no drain condition. With a decrease in the ratio of vertical-to-horizontal permeability (ky/kx = 0.1) for all drain parameters there was a decrease in the value of the dam settlement rate and the safety factor.